Chitinase 10 controls chitin amounts and organization in the wing cuticle of Drosophila. (5th August 2020) - Dong, Wei; Gao, Ying‐Hao; Zhang, Xu‐Bo; Moussian, Bernard; Zhang, Jian‐Zhen
Abstract: Wings are essential for insect fitness. A number of proteins and enzymes have been identified to be involved in wing terminal differentiation, which is characterized by the formation of the wing cuticle. Here, we addressed the question whether chitinase 10 (Cht10) may play an important role in chitin organization in the wings of the fruit fly Drosophila melanogaster . Initially, we first found that Cht10 expression coincides with the expression of the chitin synthase coding gene kkv . This suggests that the respective proteins may cooperate during wing differentiation. In tissue‐specific RNA interference experiments, we demonstrate that suppression of Cht10 causes an excess in chitin amounts in the wing cuticle. Chitin organization is severely disrupted in these wings. Based on these data, we hypothesize that Cht10 restricts chitin amounts produced by Kkv in order to ensure normal chitin organization and wing cuticle formation. In addition, we found by scanning electron microscopy that Cht10 suppression also affects the cuticle surface. In turn, cuticle inward permeability is enhanced in Cht10 ‐less wings. Moreover, flies with reduced Cht10 function are unable to fly. In conclusion, Cht10 is essential for wing terminal differentiation and function.